Review on Dam and Reservoir Optimal Operation for Irrigation and Hydropower Energy Generation Utilizing Meta-Heuristic Algorithms - Chong K.L.; Lai S.H.; Ahmed A.N.; Jaafar W.Z.W.; Rao R.V.; Sherif M.; Sefelnasr A.; El-Shafie A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Biomimetics; Computational efficiency; Dams; Electric load dispatching; Heuristic algorithms; Heuristic methods; Hydroelectric power; Hydroelectric power plants; Irrigation; Mathematical programming; Scheduling; Structural design; Water distribution systems; Water resources; Water supply; Application problems; Hydro-power generation; Meta heuristic algorithm; Non-differentiability; Problem formulation; Reservoir optimal operation; Reservoir optimizations; Scientific discipline; Reservoirs (water)